Utilization of Caesalpinia Sappan L. Extraction as A Natural Colorant in Shrimp Paste - Imalia Dwi Putri; Mardiah; Soewarno T. Soekarto (Indonesian Journal of Applied Research (IJAR), 2020)
Red shrimp paste is one of the consumers' attractions. Usually, shrimp paste uses textile dyes. The purpose of this study is to obtain a natural red pigment that is safe when applied to food products. The method used is the addition of Caesalpinia sappan extract 0.01% (w/w) and 0.02% (w/w) when compared with the control. Test parameters include water content, salt content, protein content, acid insoluble ash content, pH, hedonic organoleptic test. The results showed that the addition of Caesalpinia sappan extracts significantly affected water content (21.94% -28.06%), salinity (7.05% -6.55%), ash content (0.45% -0.48 %) and pH (6.99-6.40). The hedonic test results obtained that the preferred shrimp paste is by adding 0.02% (w/w) of Caesalpinia sappan extract with ºhue 50.11 (shrimp paste has red colour).